PENGAWASAN DEMOKRASI DESA: ANALISIS SOSIO-LEGAL ATAS NORMALISASI POLITIK UANG DAN ESKALASI KONFLIK HORIZONTAL - Kuswarini Kuswarini (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2026)
Fiscal decentralization through Law Number 6 of 2014 concerning Villages has transformed the position of Village Head into a center of accumulation of local economic-political power that systematically encourages the escalation of political costs, the normalization of money politics practices, and the proliferation of horizontal conflicts in the implementation of Village Head Elections (Pilkades). This study aims to analyze the structural failure of the Pilkades supervision system and formulate a comprehensive and legally enforceable supervision reconstruction model. The method used is normative legal research with a legislative approach and a conceptual approach, supported by a literature study of twenty nationally accredited legal scientific journals for the period 2023–2025. The analysis is based on Lawrence M. Friedman's Legal System Theory which dissects the dimensions of structure, substance, and legal culture organically. The research findings reveal three fundamental, interrelated flaws: the lack of institutional independence of the Supervisory Committee, which operates ad hoc due to its financial subordination to the Village Budget (APBDes); the absence of disqualification sanctions in regional regulations, which creates a legal blind spot at the intersection of the Village Law and the national election criminal regime; and a decadent legal culture that transforms village electoral contests into an oligarchic zero-sum game. This research recommends three reconstruction steps: vertical integration of village head election supervision under the supervision of the Regency/City Election Supervisory Agency (Bawaslu) with access to the Law Enforcement Agency (Gakkumdu); harmonization of regional regulations containing instant disqualification sanctions; and institutionalization of community-based participatory supervision supported by an anonymous digital reporting system. These findings contribute to strengthening local democratic discourse and provide a normative framework for reforming village head election supervision policies in Indonesia.